Spatial Transformation of the Higher Education System: Threats and Challenges to Single-Industry Towns - I. D. Turgel; L. L. Bozhko; M. I. Balyberdin (Высшее образование в России)
The article proposes an approach to analyzing the spatial organization of the Russian higher education system. Methodologically, the study relies on the theory of structural functionalism. In order to solve the stated research problems, the authors used comparative historical and economic-statistical analyses, as well as the quick survey method. The study characterizes the specifics of the Russian system of single-industry towns and justifies the role of a single-industry town as an integral and essential element of the settlement system. The study also reveals structural and functional changes inthe Russian system of higher education that significantly limit the possibility of preserving universities and/or their branches in single-industry towns. It was proved that the functions of higher education institutions in a single-industry town are multifaceted, complex in nature, and not limited only to the sphere of education. In spite of this, the higher education system in single-industry towns downsizes at a significantly faster rate than in the country as a whole. The performed analysis shows that the persisting trend toward increasing territorial concentration in the country’s system of higher education can create a set of negative effects that have a disruptive impact on the national settlement system, the continuity of complex value chains, and the social stability of local communities in single-industry towns. A conclusion is made about the need for comprehensive solutions regarding the development of higher education in single-industry towns that combine both national mechanisms for achieving national goals and the toolkits of regional, industrial, educational, and corporate policies.